Celebrating every learner : activities and strategies for creating a multiple intelligences classroom - Hoerr, Thomas R., 1945- (New York : Jossey-Bass, 2010)
'A practical guide to understanding how Howard Gardner's theory of Multiple Intelligences (MI) can be used in the classroom. The book describes the characteristics of each type of intelligence then provides ready-to-use lesson plans that teachers can use right away to incorporate MI in grades pre-K through 6'--
Includes bibliographical references and index.
Keywords: Elementary school teaching; Multiple intelligences; Cognitive styles; Learning; Interdisciplinary approach in education; Education -- Curricula